Deep-tissue high-sensitivity multimodal imaging and optogenetic manipulation enabled by biliverdin reductase knockout - Ludmila A. Kasatkina; Chenshuo Ma; Huaxin Sheng; Matthew Lowerison; Luca Menozzi; Mikhail Baloban; Yuqi Tang; Yirui Xu; Lucas Humayun; Tri Vu; Pengfei Song; Junjie Yao; et al. (Nature Communications)
Abstract Performance of near-infrared probes and optogenetic tools derived from bacterial phytochromes is limited by availability of their biliverdin chromophore. To address this, we use a biliverdin reductase-A knock-out mouse model (Blvra−/−), which elevates endogenous biliverdin levels. We show that Blvra⁻/⁻ significantly enhances function of bacterial phytochrome-based systems. Light-controlled transcription using iLight optogenetic tool improves ~25-fold in Blvra−/− cells, compared to wild-type controls, and achieves ~100-fold activation in neurons. Light-induced insulin production in Blvra−/− mice reduces blood glucose by ~60% in diabetes model. To overcome depth limitations in imaging, we employ 3D photoacoustic, ultrasound, and two-photon fluorescence microscopy. This enables simultaneous photoacoustic imaging of DrBphP in neurons and super-resolution ultrasound localization microscopy of brain vasculature at depths of ~7 mm through intact scalp and skull. Two-photon microscopy achieves cellular resolution of miRFP720-expressing neurons at ~2.2 mm depth. Overall, Blvra−/− model represents powerful platform for improving efficacy of biliverdin-dependent tools for deep-tissue imaging and optogenetic manipulation.